Educação e impressa em palcos republicanos : análise de jornais de Patos de Minas / MG (1889-1930) - Matos, Márcia Helena Rodrigues de (2009)
This master s degree s dissertation results from a research whose sources were newspapers published in the city of Patos de Minas, state of Minas Gerais, between 1889 and 1930. It aimed to examine the intensity of local discourses in favor of school education. According to the guidelines of the history and education historiography research line, the dealing with sources aimed to identify the social representations ascribed to education and how newspaper worked as a vehicle for the pedagogical discourses. The research development allowed to evaluate ideas spread by the press and to verify if the latter kept a link with the liberal ideas of order and progress related to the newly-created Brazilian republic. Results base the following understanding of the social changes taking place in Patos de Minas at the time: though disconnectedly newspaper articles reflected internally a conception of education promoted by the republican system; rather than defend education for all the people journalists approved the new government regime and spread the local notion of national order. In this regard, this work permit to assert that that the local press did not promoted education as way of reaching progress; rather, it adhered to the newly-established regime and acted as a transmitter of its ideology.